Assessment of high intensity ultrasound for surface decontamination of salmon (S. salar), mackerel (S. scombrus), cod (G. morhua) and hake (M. merluccius) fillets, and its impact on fish quality. (June 2017) - Pedrós-Garrido, S.; Condón-Abanto, S.; Beltrán, J.A.; Lyng, J.G.; Brunton, N.P.; Bolton, D.; Whyte, P.
Abstract: The effect of applying high intensity ultrasound on microbiological and quality parameters in several fish species was assessed at laboratory scale. Samples of salmon ( S. salar ) and mackerel ( S. scombrus ) as oily fish, and cod ( G. morhua ) and hake ( M. merluccius ) as white fish, were treated using an ultrasonic bath (30 kHz). Samples of each species were separated into three groups (i) untreated control (C), (ii) water immersion only (IM) and (iii) ultrasound (US) and treated for 5, 15, 25, 35 and 45 min. All physicochemical parameters were determined in samples treated for 45 min. Microbiological counts were reduced significantly ( p < 0.05) after US treatment in oily fish species with reductions of up to 1.5 & 1.1 log CFU/g for psychrophilic and mesophilic viable counts (PVC & TVC) observed in salmon and mackerel respectively. Corresponding reductions in white fish species were only 0.5 log CFU/g. Lipid content did not change significantly ( p > 0.05) after treatment. Significant reductions of thiobarbituric acid reactive substances (TBARS) values (C: 0.36; US: 0.18) and colour changes were observed in salmon (a* C: 12.8; US: 10.0). Moisture levels increased by 8% following US treatment in hake. Highlights: US treatment for up to 45 min significantly reduced the natural microflora of salmon and mackerel. Results of US treatments are different than IM treatments independent of microbial group in oily fish, not in white fish. Lipid content was not affected by US and IM treatments. TBARS values and colour measurements were affected by US treatments in salmon. Moisture content increased by approximately 8% in hake but did not significantly increase in salmon, mackerel or cod. Industrial relevance Fish is a highly perishable product with a short shelf-life which generates large amounts of waste and results in significant economic losses within the global seafood industry. This rapid spoilage is mainly due to the action of naturally occurring microorganisms and enzymes. From point of capture, a series of physical and chemical reactions occur, leading to a deterioration of freshness and quality of the product. Therefore, trying to retard this process while ensuring the food safety, remains a priority for the fish industry. Research on the use of non-thermal technologies has increased greatly in recent years and low-frequency ultrasound is a promising technology. Food technology processes such as extraction, curing, heating, cleaning and even microbial inactivation can be carried out using ultrasound, and is often faster and more cost effective than more traditional techniques. Therefore, the present study demonstrates the potential of high-intensity ultrasound to decontaminate the natural flora of 4 different fish species and evaluates its effect on some of the most relevant quality parameters.